Benson Relaxation Technique for Post Orif Patient on Indications of Multiple Fractures of Femur, Tibia, and Humerus Dextra: Case Study - Scintya, Fryta; Sulastini, Sulastini, (CV. Literasi Publikasi Indonesia, 2023)
Fracture is a break that occurs in bones due to trauma, often caused by traffic accidents. One of the typical symptoms of bone fractures is pain. Pain can be managed through pharmacological interventions involving the administration of medical drugs, and non-pharmacological management to reduce pain can be achieved through the Benson relaxation technique. This final scientific work aims to provide an overview of nursing care for patients with fracture disorders presenting pain issues and interventions involving the Benson relaxation technique. Descriptive analytics were employed in the form of a case study approach, utilizing nursing care approaches. Over a period of 5 days, nurses intervened in acute pain through the Benson relaxation technique. Summative evaluation results indicated that the problem was resolved. This was evidenced by a reduction in pain intensity from a scale of 5 to a pain scale of 2 (on a scale of 0-10). Based on case analysis and the application of Evidence-Based Practice, a decrease in pain intensity in Mr. R was observed by implementing the Benson relaxation technique in a post-ORIF (Open Reduction Internal Fixation) fracture case.